2020
DOI: 10.9734/ajsspn/2020/v6i230083
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Growth, Yield Components and Chemical Constituents of Chilli (Capsicum annuum L.) Plants by Using Different NPK Fertilization Levels and Nano-Micronutrients Rates

Abstract: The application of Nano micronutrient fertilizers could improve nutrient use efficiency that reduces the dosage of NPK fertilizers. This study aims to find out the best combination of NPK and Nano micronutrients fertilizers on growth, yield and quality of red hot chilli pepper. A field study was conducted on chilli (Capsicum annuum L.) fertilized by different NPK fertilization levels (0.0, 50, 75 and 100% of recommended levels) and sprayed by different Nano micronutrients rates (0.0, 0.25 and 0.50 g/l) during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Moreover, chemical constituents of safflower was increased as a result of the treatment of L-tryptophan + phenylalanine each at 150 ppm combined with K fertilization rates in comparison to those K alone or those of the other ones of combination between amino acids and fertilization in both seasons. However, Ahmed and Abdelkader (2020) indicated that chemical constituents in chilli fruits were significantly increased by using 100% recommended rate of NPK fertilizers compared to control. Also, Massoud et al (2020) found that foliar spaying with both tryptophan and glycine amino acids caused a pronounced increase in chemical constituents as compared to feverfew plants sprayed with control.…”
Section: Chemical Analysismentioning
confidence: 92%
“…Moreover, chemical constituents of safflower was increased as a result of the treatment of L-tryptophan + phenylalanine each at 150 ppm combined with K fertilization rates in comparison to those K alone or those of the other ones of combination between amino acids and fertilization in both seasons. However, Ahmed and Abdelkader (2020) indicated that chemical constituents in chilli fruits were significantly increased by using 100% recommended rate of NPK fertilizers compared to control. Also, Massoud et al (2020) found that foliar spaying with both tryptophan and glycine amino acids caused a pronounced increase in chemical constituents as compared to feverfew plants sprayed with control.…”
Section: Chemical Analysismentioning
confidence: 92%
“…Also, Abdel-kader et al (2014) found that herb fresh and dry weights/plant of lemongrass plants were significantly increased by the micronutrients mixture as foliar application compared to control. Moreover, Ahmed and Abdelkader (2020) showed that the chilli vegetative growth significantly increased by nano-micronutrients at 0.5 g/l rate compared to control. These results are in line with those found by Gomaa et al (2020) on maize.…”
Section: Effect Of Nano-micronutrientsmentioning
confidence: 94%
“…The highest yield (kg/vine) and heaviest cluster weight were correlated with nano zinc oxide treatment at 2 ppm, followed by zinc sulfate at 100 ppm, chelated zinc at 100 ppm, and chelated zinc at 200 ppm, in that order. Ahmed and Abdelkader (2020), who stated that by making it simpler for plants to absorb nutrients, nanofertilizers speed up photosynthesis and the production of dry matter. Furthermore, applying nanofertilizers to agriculture has several advantages, including faster plant absorption, enhanced development, and greater harvests (Shareef et al, 2021).…”
Section: Yield Componentsmentioning
confidence: 99%